Assessment of Partograph Utilization and its Association with Pregnancy Outcomes in Uganda. A Case of Kamwenge District - Archbald, Bahizi (British Journal of Healthcare and Medical Research, 2022)
High maternal mortality rates remain a pressing public health problem in both developed and developing countries. In Kamwenge district 120 mothers die per 100,000 live births. The use of partograph to monitor labor markedly reduces maternal and newborn deaths through early detection and management of complications. However, the level of utilization of partographs to monitor labor as well as quality and, the association between maternal and newborn outcomes with quality of partograph in Kamwenge district has never been assessed. This study assessed the level of utilization and quality of partographs in monitoring labour against pregnancy outcomes. The level of partograph use was found to be high for all health facilities. The quality of partographs was however found to be low. This study found no statistically significant association between the quality of partographs and maternal and fetal outcomes. The study concludes that health workers do not monitor certain aspects of labour using partograph and most importantly decision action are taken after crossing the action line. This may have severe implications to maternal and fetal health. To increase the use and improve the quality of partographs in monitoring labour, peer-led onsite mentorships, coaching, supervision, staff technical competence and logistics are necessary.